Inter- and Intramolecular Carbon–Carbon Bond-Forming Radical Reactions - Miyabe, Hideto (Synlett, 2012)
Free-radical-mediated reactions were studied as a powerful method for constructing the carbon–carbon bond. The intermolecular carbon radical addition to ketimines has not been widely studied. The screening of reactive ketimino radical acceptors showed that ketimines having a 2-phenolic hydroxyl group exhibit good reactivities toward nucleophilic alkyl radicals. The radical addition of these ketimines took place regioselectively at the imino carbon, providing a novel method for the construction of all-substituted sp3-hybridized carbon centers. We also found that the pyruvic hydrazone and isatin hydrazone show excellent reactivities to afford the corresponding C-alkylated products. Enantio- or diastereoselective radical addition reaction of ketimines was also tested. The control of stereochemistry in cyclization reactions has been of great importance to radical chemistry. As a cyclization that provides highly functionalized cyclic compounds, the diastereoselective cyclizations of oxime ethers were investigated. The diastereoselective radical cyclizations proceeded through a conformer that minimizes the A1,3-strain effect, and the configuration of the alkoxyamino group on the products was highly controlled by the 1,2-stereoinduction. Next, the chiral Lewis acid mediated enantioselective cyclization reactions were studied. Stereocontrol in the radical addition–cyclization–trapping reaction was achieved by the new approach, which employs hydroxamate ester functionality as a chiral Lewis acid coordinating tether between two radical acceptors. The enantioselective cascade reaction of oxime ethers also proceeded smoothly with good enantio- and diastereoselectivities. Recently, we have developed cascade reactions starting from the polarity-mismatched perfluoroalkylation of an electron-deficient acceptor with electrophilic perfluoroalkyl radicals. These cascade reactions provide a novel approach to the asymmetric synthesis of various γ-lactams.1 Introduction2 Intermolecular Radical Addition to Imine Derivatives2.1 Effect of a Phenolic Hydroxyl Group on the Reaction of Aldimine2.2 Reactivity of Ketimines Having a Phenolic Hydroxyl Group2.3 Screening of Other Ketimino Radical Acceptors3 Stereocontrolled Radical Cyclization3.1 Diastereoselective Cyclization of Oxime Ethers3.2 Stereocontrol by Using a Chiral Lewis Acid3.3 Enantioselective Cascade Reaction of Oxime Ethers3.4 Cyclization Induced by Polarity-Mismatched Perfluoroalkylation4 Conclusion
Keywords: radicals; imines; cyclizations; Lewis acids; enantioselectivity